Hubungan Konformitas, Kontrol Diri, dan Harga Diri dengan Perilaku Mencontek pada Siswa - Siti Haryati; Wiwien Dinar Pratisti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
Cheating is an act or dishonest treatment, as well as cheating to get good grades on exams or when working on questions for each lesson. With each individual must improve behavior that can minimize cheating behavior to achieve goals. This study aims to determine whether there is a relationship between the variables of conformity, self-control, and self-esteem with students' cheating behavior. The method used in this research is quantitative. There were 204 subjects in this study. The data collection tool used a scale of conformity, self-control, self-esteem, and cheating behavior. The data obtained was analyzed using multiple linear regression analysis techniques with SPSS 23 software for windows. The results of multiple regression analysis show that the sig value is 0.000, meaning that there is a correlation between conformity, self-control, self-esteem, and cheating behavior. Partially, there is no significant correlation between conformity and cheating behavior with a significant value of 0.371>0.05. There is a significant relationship between self-control and cheating behavior with a significant value of 0.010 <0.05 with an effective contribution of 0.049%. There is a significant relationship between self-esteem and cheating behavior with a significant value of 0.038<0.05 with an effective contribution of 0.032%. With it can be said that there is no significant relationship between conformity behavior and cheating behavior. And there is a significant relationship between self-control and self-esteem with cheating behavior.